A CHRISTIAN RESPONSE TO SHANKARA'S DOCTRINE OF NON-DUALITY - Muriwali Yanto Matalu (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2017)
This article describes Shankara's doctrine of non-duality and makes a Christian response. Dealing with the thought of this Indian great Philosopher is not an exaggerating effort for the concept of non- duality prevails in this New Age era. Terms such as Brahman (the absolute reality), Atman (the absolute basis of human soul which is identical to Brahman), and maya (illusion) are not peculiar to those who are familiar with the teaching of the today's New Age gurus, for instance, Deepak Chopra. Hence, my effort to react through the lens of the Christian faith will be worthwhile particularly to enrich our understanding in the realm of Christian apologetics. Here, my response shows the inherent metaphysical, logical, and ethical problems of Shankara's non-duality which he expounds in concepts like Brahman, Atman, and maya.